Efektivitas Teknik Role Playing untuk Mengembangkan Perilaku Asertif Remaja - Herny Novianti (UIN Siber Syekh Nurjati Cirebon, 2018)
This research aimed to produce effectiveness of role playing tehnicque for developing adolescence assertive behavior. The method of research used quasi-experimental research design with non-equivalent pretest-posttest control group design. The sample in this study were adolescence of Child Social Welfare Institution (LKSA) Nugraha 2015, aged 15-17 years, totaling 28 adolescents. Data was collected by assertiveness instrument, arranged on the aspects of thought, feeling, and action. The results showed role playing tehnicque effective to develop adolescence assertive behavior, increased of ten indicator. of self respect and respect for others, positive thinking, responsible for the opinions expressed, open to change, confidence, self esteem, self-acceptance, listening to others, eye contact, give and receive feedback, indicators were not significant for empathy, open body posture, and participate in the association. Recommendations showed for guidance and counseling study program, child social welfare institution (LKSA) and further research.Â